2000
DOI: 10.1016/s0092-8674(00)81561-5
|View full text |Cite
|
Sign up to set email alerts
|

OAZ Uses Distinct DNA- and Protein-Binding Zinc Fingers in Separate BMP-Smad and Olf Signaling Pathways

Abstract: We have identified the 30-zinc finger protein OAZ as a DNA-binding factor that associates with Smads in response to BMP2, forming a complex that transcriptionally activates the homeobox regulator of Xenopus mesoderm and neural development, Xvent-2. OAZ contains a BMP signaling module formed by two clusters of fingers that bind Smads and the Xvent-2 BMP response element, respectively. Previously implicated as a transcriptional partner of Olf-1/EBF in olfactory epithelium and lymphocyte development in the rat, O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
475
0
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 403 publications
(500 citation statements)
references
References 47 publications
19
475
0
4
Order By: Relevance
“…We obtained 21% identity and 50% similarity (Fig. 1a), in spite of a reduced number of 21 ZF domains compared to the 29-30 ZFs present in vertebrates Reed 1997, 1998;Hata et al 2000;Warming et al 2003Warming et al , 2004. We also confirmed that DmOAZ is the unique OAZ member in the fruit fly.…”
Section: Sequence Analysis Of a Putative D Melanogaster Oaz Homologuesupporting
confidence: 69%
See 2 more Smart Citations
“…We obtained 21% identity and 50% similarity (Fig. 1a), in spite of a reduced number of 21 ZF domains compared to the 29-30 ZFs present in vertebrates Reed 1997, 1998;Hata et al 2000;Warming et al 2003Warming et al , 2004. We also confirmed that DmOAZ is the unique OAZ member in the fruit fly.…”
Section: Sequence Analysis Of a Putative D Melanogaster Oaz Homologuesupporting
confidence: 69%
“…We also confirmed that DmOAZ is the unique OAZ member in the fruit fly. Hata et al (2000) proposed a model in which the ZF motifs of the OAZ protein are organized in clusters according to their binding ability. They identified four sets of ZFs: (1) two DNA-binding domains (cluster A: ZFs 2-8 implied in Olf/EBF pathway; cluster B: ZFs 9-13 in BMP-Smad pathway), (2) Smad-binding domain (cluster C: ZFs 14-19), (3) a cluster D with unknown function (ZFs 20-27), and (4) Olf/EBF-binding domain (cluster E; ZFs 28-30).…”
Section: Sequence Analysis Of a Putative D Melanogaster Oaz Homologuementioning
confidence: 99%
See 1 more Smart Citation
“…One such Smad partner first implicated in mediating BMP signaling is Oaz (OE/EBF-associated zinc-finger protein, also known as Znf423). This multi-zinc finger protein has been proposed to mediate signaling by means of a BMP response element (BRE) in the Xenopus vent2 gene (Hata et al, 2000). Oaz binds the BRE in vitro, and activates BMP-dependent reporter gene expression in transient transfection assays.…”
Section: Transcription Factor Partners For Smads In the Regulation Ofmentioning
confidence: 99%
“…Another link between vertebrate Schnurris and BMP signaling comes from examination of the cross-species behavior of a BRE from the Xenopus vent2 gene (Candia et al, 1997;Rastegar et al, 1999;Hata et al, 2000;Karaulanov et al, 2004;von Bubnoff et al, 2005). The BRE mediates BMP induction during frog gastrulation and is also found in the promoters of two other BMP target genes, id3 and bambi (Karaulanov et al, 2004;von Bubnoff et al, 2005).…”
Section: Schnurri Is An Evolutionarily Conserved Regulator Of Bmp Tarmentioning
confidence: 99%